If g(x) = 2x^2 - 1 what is g(x - h).

Asked on by dgplmr

2 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The function g(x) = 2x^2 - 1

g(x - h) = 2*(x - h)^2 - 1

=> 2*(x^2 + h^2 - 2xh) - 1

=> 2x^2 + 2h^2 - 4xh - 1

The expression representing g(x - h) = 2x^2 + 2h^2 - 4xh - 1

1 reply Hide Replies

ladilamborn's profile pic

ladilamborn | eNotes Newbie

Posted on

can someone please explain how this answer was figured? I don't understand at all

We’ve answered 319,814 questions. We can answer yours, too.

Ask a question